DWELLING ON POTENTIAL THREAT CUES: AN EYE MOVEMENT MARKER FOR COMBAT‐RELATED PTSD. Issue 5 (25th April 2013) - Armstrong, Thomas; Bilsky, Sarah A.; Zhao, Mimi; Olatunji, Bunmi O.
<x xml:space="preserve">Abstract</x> Background Although several studies have documented an attentional bias toward threat in posttraumatic stress disorder (PTSD), the nature of this bias has not been clearly delineated. The present study utilized eye tracking technology to delineate the time course and components of attentional bias for threat cues in combat‐related PTSD. Methods Veterans with PTSD (n = 21), combat‐exposed veterans without PTSD (n = 16), and nonveteran controls (n = 21) viewed emotional expressions (fearful, disgusted, happy) paired with neutral expressions for 3 s presentations. Results Veterans with PTSD maintained attention longer on the fearful and disgusted expressions relative to the happy expression. This negativity bias was sustained over the course of the 3 s trials, and robustly distinguished veterans with PTSD from both veterans without PTSD and nonveteran controls. Conclusions Dwelling on potential threat cues may reflect current PTSD symptoms, or it could reflect a cognitive vulnerability factor for PTSD.